Fast, Scalable Synthesis of Micronized Ge3N4@C with a High Tap Density for Excellent Lithium Storage. (28th February 2017) - Kim, Chanhoon; Hwang, Gaeun; Jung, Ji‐Won; Cho, Su‐Ho; Cheong, Jun Young; Shin, Sunghee; Park, Soojin; Kim, Il‐Doo
Abstract : Nanostructuring has significantly contributed to alleviating the huge volume expansion problem of the Ge anodes. However, the practical use of nanostructured Ge anodes has been hindered due to several problems including a low tap density, poor scalability, and severe side reactions. Therefore, micrometer‐sized Ge is desirable for practical use of Ge‐based anode materials. Here, micronized Ge3 N4 with a high tap density of 1.1 mg cm −2 has been successfully developed via a scalable wet oxidation and a subsequent nitridation process of commercially available micrometer‐sized Ge as the starting material. The micronized Ge3 N4 shows much‐suppressed volume expansion compared to micrometer‐sized Ge. After the carbon coating process, a thin carbon layer (≈3 nm) is uniformly coated on the micronized Ge3 N4, which significantly improves electrical conductivity. As a result, micronized Ge3 N4 @C shows high reversible capacity of 924 mAh g −1 (2.1 mAh cm −2 ) with high mass loading of 3.5 mg cm −2 and retains 91% of initial capacity after 300 cycles at a rate of 0.5 C. Additionally, the effectiveness of Ge3 N4 @C as practical anodes is comprehensively demonstrated for the full cell, showing stable cycle retention and especially excellent rate capability, retaining 47% of its initial capacity at 0.2 C for 12 min discharge/charge condition. Abstract : Micronized Ge3 N4 @C with a high tap density is prepared as an excellent lithium storage material. Due to the limited conversion reaction of Ge3 N4 and Li +, Ge3 N4 @C shows significantly reduced volume expansion at fully lithiated state with the high areal capacity of 2.1 mAh cm −2 and excellent reversible capacity even after 300 cycles.